HUBUNGAN TINGKAT PENGETAHUAN SADARI DENGAN PRAKTIK SADARI PADA REMAJA PUTRI DI DESA SINAR AGUNG KECAMATAN WAY TENONG KABUPATEN LAMPUNG BARAT - Titik Kurniawati; Widyah Setiyowati; Asti Puspitasari (Midwifery Care Journal, 2021)
The prevalence of cancer in Indonesia reached 1.79 per 1000 population, up from 2013 as much as 1.4 per 1000 population. This research also shows that the highest prevalence is in Yogyakarta as much as 4.86 per 1000 population, followed by West Sumatra 2.47, and Gorontalo 2.44. In women, the highest case was breast cancer at 42.1 per 100,000 population with an average death rate of 17 per 100,000. After that, cervical cancer was 23.4 per 100,000 population. The main goal of early detection of breast cancer is to find cancer in stage I level, so that the treatment becomes better. The purpose of this study was to analyze the relationship betweenbreast self-examination (BSE) knowledge level and the practice of breast self-examination (BSE). The type of research used is a correlative research with a cross sectional approach. In this study using a sampling technique on the entire population of 20 people. The results showed that most of them had good knowledge, namely 17 (85.5%) respondents, most of them did conscious practice, namely 18 (90%) respondents. There is no significant relationship between knowledge about being aware and practicing consciously as evidenced by the p value of 0.869 (p 0.05). Suggestions are aimed especially at young women to always add insight about health, especially to be aware to avoid breast cancer